Challenges and Opportunities of Pre-Service Teachers in Teaching Online during the Covid-19 Pandemic - Rahman, M Arinal; Rahmawati, Dewi; Azmi, Muhammad Nazamuddin; Saper, Md Noor; Handrianto, Ciptro; Rasool, Shahid; Kenedi, Ary Kiswanto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
Pre-service teachers must teach online due to the COVID-19 pandemic in 2020. As a result, they lacked competence, particularly in face-to-face teaching. This study aimed to discover the challenges and opportunities pre-service teachers face when the rules for online learning are enforced. This research was based on the qualitative method. Online interviews and focus group discussions with respondents were used to collect data. The respondents to this study were five students in the fifth semester of 2020 in Indonesia. The data analysis technique used Five Phases of Analysis. The results showed that the main obstacle experienced by pre-service teachers on campus was that they could not experience the face-to-face teaching process because of the COVID-19 pandemic. As a result, they were practicing online teaching. They said they were worried that when they became teachers, they would have to teach face-to-face even though they did not have enough experience doing so. However, this form of online teaching practice provides a better opportunity for pre-service teachers because they are better prepared for future forms of education where education will be integrated with technology. Pre-service teachers' experiences with online instruction during the COVID-19 showed challenges and possibilities dealt with by pre-service teachers where they can take advantage of several advantages or opportunities made available by the pandemic to help them develop into competent ICT educators. They will also have a leg up when the educational system shifts to a hybrid or fully online format in the future.